Inter- and intrapersonal skills of international hospitality professionals - Somlai, Réka (Mednarodno inovativno poslovanje, 2019)
The study focuses on extroversion personality trait and inter-and intrapersonal skills among Front Desk Agents in the hospitality industry in Hungary and Spain. The first aim of the study is to examine participants% extroversion level. The second aim is to research what the soft skills are that Front Desk Agents find important to possess to be a successful employee. International comparison is important in both focus points. Findings are based on the results of an online survey.
Keywords: cextraversion; ekstravertiranost; front desk agents; interpersonal soft skills; medosebne mehke veščine; recepcionerji; tourism; turizem